Netanyahu's strategy: a question of occupation and a dilemma of recognition - Yousef, Ayman T.; Mostafa, Mohanad (Institut Kajian Rantau Asia Barat, 2013)
This article discusses the Israeli strategy of addressing the issue of negotiation with the Palestinians during Netanyahu government 2009-2011. Netanyahu-Liebermann coalition government came after the defeat of the previous Israeli government led by Kadima political party under the chairmanship of Yahud Olmert in 2009 general election. That paved the way for the rise of the political forces that were leaning towards the Right within the Israeli political spectrum. The current Netanyahu government believes in stage-wise solution that divides the settlement with the Palestinians into two stages: the interim arrangement and the permanent solution. In order to hinder the Palestinian political endeavours under Abbas-Fayyad umbrella of internationalization of the conflict, Netanyahu began insisting that the root of the conflict is not 1967 border but 1948 confrontation. This implicitly means that the Palestinians and the Arabs must recognize the state of Israel as homeland for the Jewish people if they want Israel to recognize Palestine as a land for the Palestinians.